The grey zone: the implications of the ageing legal profession in Australia. (3rd July 2021) - Melville, Angela; Caines, Valerie; Walker, Marcus
ABSTRACT: Lawyers in many jurisdictions are ageing, and yet there is little information concerning the age profile of the legal profession. This paper presents the first consideration of the age profile of lawyers outside of the US, showing that Australian lawyers are ageing and delaying retirement. These findings have serious implications. Problems associated with a growing proportion of older lawyers include an increasing risk of lawyers suffering from age-related cognitive and physical impairment, and the related rise of complaints and malpractice claims against older lawyers. It is also clear that the Australian legal profession is unprepared to address these problems. The legal profession has ignored important gender-specific implications of ageing, such as female lawyers experiencing menopause and the lower savings of female lawyers moving into retirement. Regulatory regimes have not considered the impact of the profession's ageing profile, and there is no mandatory reporting of lawyers suffering from age-related impairment or provisions should a lawyer die. The profession also has not provided strategies to positively transition lawyers into retirement, and there is a lack of flexible working arrangements and succession planning, especially in firms located outside urban centres.